Isolation, Purification and Structural Characterestics of Chondroitin Sulfate from Smooth hound Cartilage: In vitro Anticoagulant and Antiproliferative Properties. (1st October 2018) - Krichen, Fatma; Bougatef, Hajer; Sayari, Nadhem; Capitani, Federica; Ben Amor, Ikram; Koubaa, Imed; Maccari, Francesca; Mantovani, Veronica; Galeotti, Fabio; Volpi, Nicola; Bougatef, Ali
Highlights: The chondroitin sulfate was extracted and purified from Smooth hound cartilage (CSSH). The physicochemical and Structural characteristics of CSSH were determined by acetate cellulose electrophoresis, FTIR, 13 C NMR and SAX-HPLC. CSSH has high sulfate amount and a relatively average molecular mass. CSSH showed strong anticoagulant and antiproliferative properties. Abstract: Chondroitin sulfate was extracted from the cartilage of smooth hound (CSSH) and then purified by anion exchange chromatography. The structual characteristic of CSSH was evaluated by acetate cellulose electrophoresis, FTIR, 13 C NMR and SAX-HPLC. Molecular weight of CSSH was average 68.78 KDa. Disaccharide analysis indicated that CSSH was predominately composed of monosulfated disaccharides in position 6 and 4 of the N-acetylgalactosamine (45.34% and 32.49%, respectively). CSSH was tested for in vitro anticoagulant activity using the three classical coagulation assays (activated partial thromboplastin time (aPTT), prothrombine time (TT) and thrombin time (PT) tests). The finding showed that CSSH prolonged significatively (p < 0.05), aPTT, TT and PT about 1.4, 3.44 and 1.21 fold, respectively, greater than that of the negative control at a concentration of 100 μg/ml. The CSSH caused a significant antiproliferative activity against HCT116 cell, which was 79% of cell proliferation inhibition at the concentration of 1000 μg/ml. Further, CSSH presented no toxicity against the normal cells and no hemolysis towards bovine erythrocytes for all concentrations tested. CSSH demonstrated hopeful antiproliferative and anticoagulant potential, which may be used as a novel and effective drug.